2024
DOI: 10.1098/rsos.231616
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy break, sprouting and later tuber reproduction in response to different tuber sizes of tiger nut (Cyperus esculentusL.)

Binshuo Liu,
Hanbo Li,
Wei Chen
et al.

Abstract: Dormancy release pattern, sprout growth and later reproduction were studied among various tuber sizes of Cyperus esculentus to determine effective methods to release dormancy and further to select suitable tuber size of this species in production. The results showed that medium tubers performed better during sprouting than large and small tubers under all pre-sprouting treatments. Pre-sprouting treatments at 25°C, 35°C, RT (room temperature) and −2°C were effective in relieving dormancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The treatments with 10 mg L −1 GA, 100 µL ethylene, and bud cutting did not differ from the control. Liu et al [26] reported, in their study, that the variation in tuber size influences the growth and development of yellow nutsedge plants. According to the authors, tuber size was identified as one of the main factors influencing dormancy breakage.…”
Section: Effect Of Dormancy-breaking Treatments On the Initial Develo...mentioning
confidence: 98%
“…The treatments with 10 mg L −1 GA, 100 µL ethylene, and bud cutting did not differ from the control. Liu et al [26] reported, in their study, that the variation in tuber size influences the growth and development of yellow nutsedge plants. According to the authors, tuber size was identified as one of the main factors influencing dormancy breakage.…”
Section: Effect Of Dormancy-breaking Treatments On the Initial Develo...mentioning
confidence: 98%